Zbigniew Fras, Galicja, Wrocław 2000, Wydawnictwo Dolnośląskie, ss. 300 - Antczak, Stanisław (Biuletyn Historii Wychowania, 2000)
Zbigniew Fras, Galicja, Wrocław 2000, Wydawnictwo Dolnośląskie, ss. 300